Collagen-producing lung cell atlas identifies multiple subsets with distinct localization and relevance to fibrosis - Tsukui, Tatsuya; Sun, Kai-Hui; Wetter, Joseph B.; Wilson-Kanamori, John R.; Hazelwood, Lisa A.; Henderson, Neil C.; Adams, Taylor S.; Schupp, Jonas C.; Poli, Sergio D.; Rosas, Ivan O.; Kaminski, Naftali; Matthay, Michael A.; et al. (Nature communications, 2020)
Collagen-producing cells maintain the complex architecture of the lung and drive pathologic scarring in pulmonary fibrosis. Here we perform single-cell RNA-sequencing to identify all collagen-producing cells in normal and fibrotic lungs. We characterize multiple collagen-producing subpopulations with distinct anatomical localizations in different compartments of murine lungs. One subpopulation, characterized by expression of Cthrc1 (collagen triple helix repeat containing 1), emerges in fibrotic lungs and expresses the highest levels of collagens. Single-cell RNA-sequencing of human lungs, including those from idiopathic pulmonary fibrosis and scleroderma patients, demonstrate similar heterogeneity and CTHRC1 -expressing fibroblasts present uniquely in fibrotic lungs. Immunostaining and in situ hybridization show that these cells are concentrated within fibroblastic foci. We purify collagen-producing subpopulations and find disease-relevant phenotypes of Cthrc1 -expressing fibroblasts in in vitro and adoptive transfer experiments. Our atlas of collagen-producing cells provides a roadmap for studying the roles of these unique populations in homeostasis and pathologic fibrosis. Collagen production by lung cells is critical to maintain organ architecture but can also drive pathological scarring. Here the authors perform single cell RNA sequencing of collagen-producing lung cells identifying a subset of pathologic fibroblasts characterized by Cthrc1 expression which are concentrated within fibroblastic foci in fibrotic lungs and show a pro-fibrotic phenotype.